solve by substitution method 8x +3y = 11, 3x -y =2
Answers
Answered by
31
see the image for the answer
Attachments:
![](https://hi-static.z-dn.net/files/de8/31fe2f16c9e8c8406fc654d696b47923.jpg)
Preeti00:
thanks
Answered by
71
Hello friends..
____________________________
==> 8x + 3y = 11 ....................(I)
==> 3x - y = 2 ...................(II)
In equation (II) it is easy to express y in terms of x.
3x - y = 2
3x -2 = y
Substituting y = 3x - 2 in equation (I)
8x + 3y = 11
8x + 3(3x - 2) = 11
8x + 9x - 6 = 11
17x - 6 = 11
17x = 11+6
17x = 17
x = 17/17
x = 1
Now,substituting the value of x in the equation y = 3x - 2
y = 3x - 2
y = 3 x 1 - 2
y = 3 - 2
y = 1
So,x = 1 and y = 1 are the solution of the given equation..
Thanks..
:)
____________________________
==> 8x + 3y = 11 ....................(I)
==> 3x - y = 2 ...................(II)
In equation (II) it is easy to express y in terms of x.
3x - y = 2
3x -2 = y
Substituting y = 3x - 2 in equation (I)
8x + 3y = 11
8x + 3(3x - 2) = 11
8x + 9x - 6 = 11
17x - 6 = 11
17x = 11+6
17x = 17
x = 17/17
x = 1
Now,substituting the value of x in the equation y = 3x - 2
y = 3x - 2
y = 3 x 1 - 2
y = 3 - 2
y = 1
So,x = 1 and y = 1 are the solution of the given equation..
Thanks..
:)
Similar questions
Psychology,
9 months ago
Science,
9 months ago
Math,
1 year ago
English,
1 year ago
Hindi,
1 year ago